Performance evaluation of selected locally available cement in stabilizing soil for pavement base purposes. - Victor, Jaime Angelo S.
Cement treated base course are commonly used in high volume and load traffic areas, such as: airports, industrial areas, and major highways. Various materials such as soil, aggregates and recycled concrete may be treated with cement to improve its engineering properties. This study aims to investigate the effect of cement type and cement content to the strength properties of soil cement used as base courses of pavements. The strength parameter considered in this study is the soaked unconfined compressive strength, with minor testing for California Bearing Ratio (CBR). Soil samples from A-2-4 type of soil were used to produce cylindrical soil-cement specimens to be used for standard compressive strength tests. Results show that for all cement types, there were significant increases in compressive strength of the soil cement samples for every 2% increment of cement content. In comparison with each other, there were significant 28-day strength differences among samples of varying cement type but with one cement content. Type I soil cement samples demonstrated high early strength and satisfied the DPWH strength standard at the PCA recommended cement contents for design (5%, 7% and 9%). With regard to the CBR, all the samples satisfied the DPWH standard of a minimum 100% CBR.
Keywords: Pavements, Soil-cement.